Influence of immunomodulator Immunobeta on the humoral immunity of lambs during the thermoneutral, hot, and cold season - Bozakova, N; Sotirov, L; Koynarski, T; Ivanov, V (Journal of the Hellenic Veterinary Medical Society, 2025)
Infectious diseases cause devastating economic losses in the sheep industry. The current study aimed to evaluate blood serum concentrations of lysozyme, gamma interferon, immunoglobulin G, immunoglobulin M, cortisol, serotonin, the activity of the alternative pathway of complement activation (APCA), and betalysin activity in lambs, whose rations were supplemented with 4g /kg immunomodulator Immunobeta for 60 days - from the 15th day to the 75th day after birth in manure-pasture cultivation during a thermoneutral, hot summer and cold winter period. The lambs were divided into two groups - control and experimental. To the experimental animals, after 15 days of age, the immunomodulator Immunobeta was added to the standard concentrated feed, at a dose of 4g/kg feed. It was found that the immunomodulator Immunobeta reliably increases the values of the investigated indicators in all three annual seasons. It could be concluded that the studied immunomodulator Immunobeta possesses an important immunomodulating potential in lambs, which could improve their health.